Transforming Growth Factor β Up-regulates Cysteine-rich Protein 2 in Vascular Smooth Muscle Cells via Activating Transcription Factor 2 - Lin, Da-Wei (American Society for Biochemistry and Molecular Biology, 2008)
CRP2 (cysteine-rich protein) is a vascular smooth muscle cell (VSMC)-expressed LIM-only protein. CRP2 associates with the actin cytoskeleton and interacts with transcription factors in the nucleus to mediate smooth muscle cell gene expression. Using Csrp2 (gene symbol of the mouse CRP2 gene)-deficient mice, we previously demonstrated that an absence of CRP2 enhances VSMC migration and increases neointima formation following arterial injury. Despite its importance in vascular injury, the molecular mechanisms controlling CRP2 expression in VSMC are largely unknown. Transforming growth factor β (TGFβ), a key factor present in the vessel wall in the early phases of arterial response to injury, plays an important role in modulating lesion formation. Because both CRP2 and TGFβ are mediators of VSMC responses, we examined the possibility that TGFβ might regulate CRP2 expression. TGFβ significantly induced CRP2 mRNA and protein expression in VSMCs. Promoter analysis identified a conserved cAMP-responsive element (CRE)-like site (TAACGTCA) in the Csrp2 promoter that was critical for basal promoter activity and response to TGFβ. Gel mobility shift assays revealed that mainly ATF2 bound to this CRE-like element, and mutation of the CRE sequences abolished binding. TGFβ enhanced the activation of ATF2, leading to increased phospho-ATF2 levels within the DNA-protein complexes. Furthermore, ATF2-transactivated Csrp2 promoter activity and TGFβ enhanced this activation. In addition, a phosphorylation-negative ATF2 mutant construct decreased basal and TGFβ-mediated Csrp2 promoter activity. Our results show for the first time in VSMC that TGFβ activates ATF2 phosphorylation and Csrp2 gene expression via a CRE promoter element.